Sources of increased variability in world cereal production since the 1960s - Hazell, Peter B. R. (Wiley, 1985)
Recent growth in world cereal production has been accompanied by a more than proportional increase in the standard deviation of production. This study applies variance decomposition procedures to data on crop production by major geographical regions of the world to analyse the sources of this increased instability. It is found that the increase in aggregate production variability is predominantly due to increased yield variability and to a simultaneous loss in offsetting patterns of variation in yields between crops and regions. These changes are probably associated with the sharp increase in the variability of world cereal and oil prices since the early 1970s and with the more widespread adoption of improved seed/fertiliser intensive technologies.